2007
DOI: 10.1002/macp.200700229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Curing on Electrical Properties of a UV‐Curable co‐Polyacrylate/Silica Nanocomposite as a Transparent Encapsulation Resin for Device Packaging

Abstract: Electrical properties of UV‐curable co‐polyacrylate/silica nanocomposite resins prepared via sol‐gel process for device encapsulation were investigated. It was found that, by appropriate UV curing process and the formation of nanoscale silica particles finely dispersed in the resin matrix, the leakage current density of the nanocomposite resin films decreases from 235 to 1.3 nA · cm−2 at the applied electrical field of 10 kV · cm−1. The silica nanoparticles also restricted the motions of polar functional group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…It is speculated that the too many Ta 2 O 5 particles may hinder the propagation of UV light into the interior of nanocomposites and thus cause the incomplete sample curing. A prolonged curing time was thus required for high‐filler‐loading samples; nevertheless, excessive UV exposure might induce the photo‐degradation of polymer matrix and lead to the degradation of thermal stability of nanocomposite samples 30–32…”
Section: Resultsmentioning
confidence: 99%
“…It is speculated that the too many Ta 2 O 5 particles may hinder the propagation of UV light into the interior of nanocomposites and thus cause the incomplete sample curing. A prolonged curing time was thus required for high‐filler‐loading samples; nevertheless, excessive UV exposure might induce the photo‐degradation of polymer matrix and lead to the degradation of thermal stability of nanocomposite samples 30–32…”
Section: Resultsmentioning
confidence: 99%
“…Seldom have reports involved the modification of SL resins with nanomaterials. On the other hand, many papers [22][23][24][25][26][27][28] have reported that nanomaterials show considerable improvement or novel performance compared with traditional materials. Therefore, Sandoval et al [29] and Sandoval and Wicker [30] successfully prepared SL nanocomposites using Somos 11120, 10110, and multi-walled carbon nanotubes, and investigated the mechanical properties of the modified SL resins.…”
Section: Introductionmentioning
confidence: 99%
“…Many silicon components have been applied to non-UV curing systems, while there are only several types incorporated into the UV-curable, such as organosilicone-containing hybrid systems [13][14][15] and inorganicorganic silicon hybrid. 3,5,16,17 Those used silicon components still do not seem to present large numbers of photosensitive groups or more efficiently enhance the properties of UV-cured coatings. Polysiloxanes are capable not only of providing two sites for crosslinks, but also of forming functional chains through bond formation with silicon.…”
Section: Introductionmentioning
confidence: 99%